New evidence on the underrepresentation of Asian Americans in leadership positions - Zhu, Maria (IZA - Institute of Labor Economics, 2023)
For decades, Asian Americans have been characterized as a
10419/278928
Keywords: Graue Literatur; Asian Americans; leadership; labor market outcomes